STRATEGI GURU PAI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA KELAS XI MAN 1 MANDAILING NATAL - Zainuddin Hasibuan; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to evaluate the strategies employed by Islamic Education teachers at MAN 1 Mandailing Natal to enhance students' Quran reading skills. The research utilizes a qualitative method with a descriptive approach, gathering data through observation, documentation, and interviews. Findings indicate varying levels of Quran reading proficiency among students, with teaching strategies including habitual Quran reading before lessons, grouping students by ability, and employing the listen-and-repeat Quran reading method. Supportive factors for these strategies include the role of the school principal, parental involvement, the presence of Quran recitation extracurriculars, and high student motivation in Quran learning. Conversely, challenges include a lack of Quran learning resources, limited PAI lesson time, and insufficient educational media facilities. Results from these strategies show gradual improvements in students' Quran reading abilities.